An association analysis between a polymorphism in the SEC24A gene and lipid traits recorded in Duroc pigs. Issue 1 (1st January 2021) - Mármol-Sánchez, Emilio; Quintanilla, Raquel; Luigi-Sierra, María Gracia; Amills, Marcel
Abstract: By regulating the expression of low-density lipoprotein receptors (LDLR), the SEC24A protein modulates the clearance of plasma cholesterol in mice. The whole-genome sequencing of five Duroc boars that sired a Duroc purebred experimental population (LIPGEN population, 350 individuals) revealed the segregation of one putative nonsense mutation located at the SEC24A (rs336401826, c.44G>A) gene. Genotyping of this polymorphic site in the LIPGEN population highlighted the existence of a significant departure from the Hardy Weinberg equilibrium ( χ 2 = 5.05, p -value = 0.024527). Despite the fact that SEC24A inactivation should affect serum lipid concentrations, we did not observe an association between SEC24A genotype and such traits. A thorough revision of the annotation of the SEC24A rs336401826 SNP revealed that this polymorphism is probably located in the 5'UTR of the SEC24A gene, rather than at the beginning of the first exon, hence not introducing the predicted premature stop codon that could truncate the SEC24A protein. Given that the annotation of loss-of-function mutations in pigs is far from perfect, careful manual curation of such mutations is recommended before undertaking the analysis of their effects at the experimental level. HIGHLIGHTS: One mutation (c.44 G>A) predicted to disrupt the SEC24A protein segregates in a Duroc pig population. This polymorphism is not associated with serum lipid levels despite its expected effect on such traits. Manual curation of the annotation of this putative nonsense polymorphism has revealed that it maps to the 5'UTR of the SEC24A gene.